Public value and performance of libraries - Seppänen, Antti; Laitinen, Markku; Rajala, Tomi; Laihonen, Harri (Qualitative and Quantitative Methods in Libraries, 2019)
This paper addresses the changing role of libraries as central knowledge hubs of an information society. It questions the relevance of the existing performance measures and asks what kind of public value we are expecting from the libraries. The paper illustrates its main arguments with the empirical context of the Finland and shortly introduces the case of ‘Iso Omena’ in Espoo, Finland where a novel approach for providing public value has been implemented. The paper develops two arguments to guide the future research in the area. First, new indicators and measurement practices are needed if we want to evaluate more comprehensively the public value of libraries. Second, performance management and evaluation taking place in libraries calls for active performance dialogue between the relevant interest groups in order to determine the public value of libraries and performance measures tracking how this value is produced.